Effects of GABAA Receptor α3 Subunit Epilepsy Mutations on Inhibitory Synaptic Signaling - Syed, Parnayan; Durisic, Nela; Harvey, Robert J.; Sah, Pankaj; Lynch, Joseph W. (Frontiers in Molecular Neuroscience, 2020)
Missense mutations T166M, Q242L, T336M, and Y474C in the GABAA receptor (GABAAR) α3 subunit gene are associated with epileptic seizures, dysmorphic features, intellectual disability, and developmental delay. When incorporated into GABAARs expressed in oocytes, all mutations are known to reduce GABA-evoked whole-cell currents. However, their impact on the properties of inhibitory synaptic currents (IPSCs) is unknown, largely because it is difficult to establish, much less control, the stoichiometry of GABAAR expressed in native neuronal synapses. To circumvent this problem, we employed a HEK293 cell-neuron co-culture expression system that permits the recording of IPSCs mediated by a pure population of GABAARs with a defined stoichiometry. We first demonstrated that IPSCs mediated by α3-containing GABAARs (α3β3γ2) decay significantly slower than those mediated by α1-containing isoforms (α1β2γ2 or α1β3γ2). GABAAR α3 mutations did not affect IPSC peak amplitudes or 10–90% rise times, but three of the mutations affected IPSC decay. T336M significantly accelerated the IPSC decay rate whereas T166M and Y474C had the opposite effect. The acceleration of IPSC decay kinetics caused by the T366M mutation was returned to wild-type-like values by the anti-epileptic medication, midazolam. Quantification experiments in HEK293 cells revealed a significant reduction in cell-surface expression for all mutants, in agreement with previous oocyte data. Taken together, our results show that impaired surface expression and altered IPSC decay rates could both be significant factors underlying the pathologies associated with these mutations.